Experimental Investigation of Frozen Solid State Drive on Digital Evidence with Static Forensic Methods - Riadi, Imam; Umar, Rusydi; Nasrulloh, Imam Mahfudl (Lontar Komputer : Jurnal Ilmiah Teknologi Informasi, 2018)
The rapid development of computer technology in hardware, is currently developing non-volatile computer storage media Solid State Drive (SSD). SSD technology has a faster data access speed than Hard Disk and is currently starting to replace Hard Disk storage media. Freezing software on computer systems is often carried out by computer technicians, because it can save a computer maintenance costs due to errors, be exposed to computer viruses or malware. This software is used to prevent unwanted changes to the computer system, when the computer is restarted changes that occur in the computer system will not be stored on storage media. When this happens, what should be done by digital forensic investigators. This study discusses experimental forensic investigations on SSD media storage with frozen conditions or in this study said the frozen SSD. Frozen SSD is the condition of the drive that is locked so that there is no change in the computer system. Software used to lock and prevent changes such as Deep Freeze, Shadow Defender, Windows Steady State, and Toolwiz Time Freeze . Forensic research stages using methods NIST. The result shows that from comparative analysis conducted with Deep Freeze the results of the RecoverMyFile gives 76 . 38 % and Autopsy gives 75 ,27 %, while frozen condition with Shadow Defender the results of the RecoverMyFile gives 5 9 . 72 % and Autopsy gives 74 . 44 %. So the results of this study indicate the drive freezing software has an effect obtained can be an obstacle in the digital forensic process.